ANALISIS PENGARUH ATRIBUT PRODUK SEPEDA MOTOR TERHADAP PERILAKU KONSUMEN - Suryadi Suryadi; Ludfi Djajanto (Adbis: Jurnal Administrasi dan Bisnis, 2020)
The purpose of this study is to determine and analyze the factors of price perspective attributes, brand benefits, media branding, promotions, after-sales guarantee, products, colors, and designs as well as fuel consumption as items of motor products on consumer behavior. The sampling technique used in this study was purposive sampling with a sample size of 194 respondents. The data analysis was using descriptive analysis and multiple linear regression analysis using SPSS software. The results showed that Honda's products were more dominant in the implementation of its marketing strategy with a contribution of 87.75% while the attributes of Yamaha's products contributed to the influence of the remaining 79.40% influenced by other factors. In addition, the results of the analysis obtained a regression equation for Honda products Y = -13.33 + 0.428 X1 - 0.035 X2 + 0.02 X3 + 0.319 X4 + 0.01 X5 + 0.367 X6 - 0.03 X7 + 0.034 X8, while for Yamaha products are Y = -13.03 + 0.37 X1 + 0.5 X2 + 0.11 X3 + 0.30 X4 - 0.004 X5 + 0.33 X6 - 0.13 X7 + 0.2X8.